Oxidation behaviour of 18/8 Cr-Ni austenitic steel in presence of Na2SO4 and NiSO4 at 650 to 1000°C - Anees, Udin Malik; Mohammed Misbahul, Amin; Sharif, Ahmad (Carl Hanser Verlag, Germany, 2009)
Link to publisher's homepage at http://www.materialography.de/PractMet/Archive/2008/index.php?id=g